Autochthonous Paget’s bone disease: A case report - Gutiérrez-Zúñiga, Daniela; Arbeláez-Echeverry, Pablo; Caicedo, Beatriz; Messa, Oscar A. (Revista Colombiana de Ortopedia y Traumatología, 2022)
Paget’s disease of bone is a metabolic alteration due to an imbalance between osteoclastic and osteoblastic activity, leading to an inefficient remodeling process that results in changes in bone structure. Although in many cases it can be asymptomatic, it is associated with severe complications such as fractures, skeletal deformities, bone neoplasms and symptoms due to compression of nerve structures at the skull and spine. This pathology occurs more frequently in male patients and in the United Kingdom, as well as in countries with a British immigrant population; however, it is very infrequent in Latin American countries. We present the case of a 72-year-old patient diagnosed with Paget’s disease according to imaging and laboratory findings, treated with zoledronic acid for symptomatic management.